Influence of pressure on filtration performance of nanofiber composite filtering material - Xianzhao WANG; Changfeng XU; Kang JI; Rongjun SONG; Yunxin ZHANG; Cheng CHANG; Zhongli JI (You-qi chuyun, 2022)
Purification technology is required to separate the liquid impurities of natural gas during its transportation. However, the filtration performance of coalescing filter element used for natural gas purification at present needs to be improved. Therefore, the new filtering materials were developed by a nanofiber composite method. Besides, the permeability and gas-liquid filtration performance of the 4 types of composite filtering materials were tested with the experimental devices under the pressures from 0.1 MPa to 0.5 MPa. The results show that the Darcy coefficient of the composite filtering materials decreases with the increasing of the surface density of nanofiber, and more significant decrease is observed after the substrate with high permeability is composited with the nanofiber. Meanwhile, the increasing of operating pressure can lead to the compression of filtering material structure, which further results in the change of the mutual relationship between the Darcy coefficient and non-Darcy coefficient. Moreover, the filtration efficiency of filtering materials is improved after compositing with nanofiber, but the pressure drop also increases. Under the condition of same surface density of nanofiber, the pressure drop in oleophobic filtering material is more significant than the oleophilic filtering material. Hence, too high surface density will result in excessive pressure drop, further causing the reduction of the comprehensive performance of filtering materials. Generally, the research results could provide reference for the selection of filtering materials for natural gas purification.